Akibat Hukum dari Perjanjian yang Dibuat dengan Tanggal Mundur (Back Date) - Nathanael, Moses; Djaja, Benny (UNES Law Review, 2023)
Back date agreement is an agreement made to accommodate past legal actions. The back date agreement is basically made based on the agreement of the parties so that it generally does not cause harm to the parties. Problems arise if this back date agreement is made in the form of an authentic deed, this is because Article 16 paragraph (1) letter m of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions states that: In carrying out his position, the Notary is obliged to: read the deed before an appearance in the presence of at least 2 (two) witnesses, or 4 (four) witnesses specifically for the making of an underhand will, and signed at the same time by the appearer, witness, and Notary." The results of this study indicate that agreements made on a back date, both in the form of oral agreements, underhand deeds, and authentic deeds, basically have fulfilled the legal requirements of the agreement as referred to in Article 1320 of the Civil Code, so that it has legal.